IMPLEMENTASI MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) UNIVERSITAS DARUSSALAM GONTOR (UNIDA) PONOROGO - Mohammad Zakki Azani; Mohammad Ali; Ari Susanto; Muhammad Rasyidil Fikri Alhijri; samsirin samsirin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
In essence, the application of MBKM is a very essential form of student-centered learning. In its development, the UNIDA campus has twice participated in the Teaching Campus, one of the MBKM programs held by the Minister of Education. The purpose of this study was to determine the extent of implementation and obstacles in MBKM on the campus of Darussalam Gontor University, Ponorogo (UNIDA) as well as some of the problems and obstacles in it. This research uses a case study approach. The instrument of data collection was done by interview, and documentation. The results of this study show that although UNIDA has started to implement several MBKM activities, they are still not running optimally due to several things including: (1) there is no strong legal umbrella to state that the academic community makes other policies related to the implementation of MBKM itself; (2) socialization, which is felt to be very lacking; (3) unclear credit conversion, (4) differences in the use of the year used by UNIDA in determining the academic calendar, where Unida uses the Hijri calendar while in general MBKM activities are based on the Masehi Calender.